Distinct Circulating Expression Profiles of Long Noncoding RNAs in Heart Failure Patients With Ischemic and Nonischemic Dilated Cardiomyopathy - Lin, Fang; Gong, Xin; Yu, Ping; Yue, Aixue; Meng, Qingshu; Zheng, Liang; Chen, Tian; Han, Lu; Cao, Hao; Cao, Jianhong; Liang, Xiaoting; Hu, Hao; et al. (Frontiers in Genetics, 2019)
Ischemic cardiomyopathy (ICM) and dilated cardiomyopathy (DCM), with distinct long-term prognosis and responses to treatment, are two major problems that lead to heart failure (HF) ultimately. In this study, we investigated the lncRNA and mRNA expressions in the plasma of patients with DCM and ICM and analyzed the different lncRNA profile between the two groups. The microarray analysis identified 3222 and 1911 significantly differentially expressed lncRNAs and mRNAs between DCM and ICM group. The most enriched up-regulated functional terms included positive regulation of I-kappaB kinase/NF-kappaB signaling and regulation of cellular localization, while the top 10 down-regulated genes mainly consisted of acid secretion and myosin heavy chain binding. Furthermore, the KEGG pathway analysis revealed that the differentially expressed lncRNA-coexpressed mRNAs between DCM and ICM group were significantly enriched in the natural killer cell mediated cytotoxicity and ras signaling pathway respectively. qRT-PCR confirmed 8 of 12 LncRNAs were upregulated in DCM group compared to ICM group which was consistent with the initial microarray results. The lncRNA/mRNA coexpression network indicated the possible functions of the validated lncRNAs. These findings revealed for the first time the specific expression pattern of both protein-coding RNAs and lncRNAs in plasma of HF patients due to DCM and ICM which may provide some important evidence to conveniently identify the etiology of myocardial dysfunctions and help to explore a better strategy for future HF prognosis evaluation.